Comparative analysis of clinical and arthroscopic findings in ACL injury of the knee - Kostova, Elena; Kostov, Hristijan; Stojmenski, Slavcho; Hasani, Ilir; Gavrilovski, Andreja (My University, 2014)
Background: This study was conducted to compare accuracy of MRI findings taking arthroscopy as standard in knee injuries. Methods: All patients attending our hospital with knee injury underwent clinical examination. Out of them 100 patients with knee injury were subjected to clinical examination, MRI and then Arthroscopy. The results were compared and analyzed using various statistical tests. The accuracy, sensitivity and specificity were calculated based on these arthroscopic and MRI findings. Results: The accuracy of clinical diagnosis in our study was 88% for ACL tears and 85% for meniscal tears. Our study proved high sensitivity and specificity and almost high accuracy for ACL injuries of knee joint in comparison to arthroscopy. MRI is an excellent screening tool for therapeutic arthroscopy. We can avoid diagnostic arthroscopy in patients with knee injuries having equivocal clinical and MRI examination and go on for therapeutic modality. Conclusions: For the assessment of ligamentous and meniscal injuries magnetic resonance imaging (MRI) is accurate and noninvasive modality. It can be used as a first line investigation but arthroscopy still remains gold standard in diagnosing ACL and meniscal injuries.
Keywords: arthroscopy; ACL; MRI; meniscus; knee